Implementasi Pembelajaran Berdiferensiasi dengan Model PBL pada Pelajaran PAI - Nurul Annisa; Askar Askar; Sagir Muhammad Amin; Andi Anirah; Nasrul Nasrul (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
Differentiated learning using the Problem Based Learning (PBL) model is one of the innovative strategies implemented to meet the diverse learning needs of students in the classroom. This study examines the implementation of differentiated learning with the PBL model in Islamic Religious Education and Character Education subjects at SMAN 4 Palu, aiming to understand how the integration of these two approaches affects the learning process and student learning outcomes. The method used is a qualitative approach, which includes observation, in-depth interviews, and documentation, as well as descriptive qualitative data analysis techniques to gain a comprehensive understanding of the experiences of students and teachers in implementing differentiated PBL. The results show that the approach is able to increase student engagement in learning, facilitate the development of critical thinking skills, and increase learning motivation, although there are some challenges in adapting the model to the subject matter. In conclusion, the implementation of differentiated PBL has great potential to improve the quality of learning and student learning outcomes as a whole.